PERCEPTION OF UNDERGRADUATE MEDICAL STUDENTS ABOUT DIFFERENT FORMATS OF ASSESSMENT IN SUBJECT OF PATHOLOGY - Hijab Batool; Asim Mumtaz; A.S Chughtai (Journal of University Medical & Dental College, 2017)
Abstract: Objective: To explore students’ perspective on different methods of assessment in the subject of pathology at Central Park Medical College Lahore. Background: In medical education, assessment is entering every phase of professional development. In Pakistan, medical undergraduates are assessed by four methods; MCQs, SEQs, Viva voce and OSPE. All of these methods help to assess the clinical knowledge and cognitive skills of the medical professionals. Materials and methods: This study was conducted among third year (n=105) and fourth year(n=114) undergraduate medical students of Central Park Medical College. A questionnaire was distributed among the participants to find out the most preferred method of assessment in the subject of Pathology. The students were explained about the aim of study and 15 minutes were given to fill the questionnaire. The responses were analyzed by using percentages. Results: This study revealed that according to participants, the most useful tool of assessment during a class test of Pathology is MCQs (54.3%) followed by SEQs (36.9%). Viva voce and OSPE were not preferred to a greater extent during a pathology class test (14% and 5% respectively), statistical difference between all four perceptions about tools proved to be significant as p < 0.0001. For University examination in the subject of Pathology, the least useful method of assessment according to participants is OSPE (52.3%). The second least beneficial option for a Pathology Annual University examination selected by the students was Viva Voce (24.4%) followed by SEQs and MCQs (14.2% and 9.1% respectively), statistical difference between all four perceptions about tools proved to be significant as p < 0.0001. Conclusion: The findings of this study revealed that according to undergraduate students of Central Park Medical College, MCQs during a pathology class test can assess their knowledge in a better way as compared to other tools of assessment. On the other hand the students who have passed the university examination of pathology selected OSPE as the least useful tool of assessment during annual professional examination.